Some problems of ensuring the human right to life: a comparative analysis of the theory of law and theories of criminal law (Journal of actual problems of jurisprudence, 2019)
The article reveals the theoretical issues of ensuring the right to life and determining the beginning of life. A comparative analysis of criminal law relating to the beginning of life in foreign countries. The conclusion is formulated that it is necessary to fix on legislative basis requirements for the lifestyle of a pregnant woman in order to have a full-fledged child.